2021
DOI: 10.1007/s11356-021-14316-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of straw retention on carbon footprint under different cropping sequences in Northeast China

Abstract: Inappropriate farm management practices can lead to increased agricultural inputs and changes in atmospheric greenhouse gas (GHG) emissions, impacting climate change. This study was initiated in 2012 to assess the potential for straw retention to mitigate the negative environmental impact of various cropping systems on the Songnen Plain using the life cycle assessment (LCA) method combined with field survey data. Straw retention (STR) and straw removal (STM) treatments were established in continuous corn (CC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
(79 reference statements)
1
2
0
Order By: Relevance
“… Shi-hao Li et al (2020) found that in rice-wheat rotation, annual CH 4 emission increased by 5.4%–72.2% with the straw return-to-field and carbon emission (4,275–4,989 kg CO 2 -eq ha −1 ) also increased with increasing straw returning amounts ( Li S. H. et al, 2020 ). Similar result confirming the positive correlation between straw and soil carbon footprint was also discovered by Xuening Song et al (2021) that assessed the effects of straw retention and straw removal on carbon footprint of continuous corn cropping and corn-soybean rotation ( Song Q. et al, 2021 ). Hence, straw return-to-field usually gives rise to GHG emissions from the soil and increase carbon footprint of agricultural activity ( Dhaliwal et al, 2019 ).…”
Section: Reduction Of the Carbon Footprint Of Straw Return-to-field B...supporting
confidence: 84%
“… Shi-hao Li et al (2020) found that in rice-wheat rotation, annual CH 4 emission increased by 5.4%–72.2% with the straw return-to-field and carbon emission (4,275–4,989 kg CO 2 -eq ha −1 ) also increased with increasing straw returning amounts ( Li S. H. et al, 2020 ). Similar result confirming the positive correlation between straw and soil carbon footprint was also discovered by Xuening Song et al (2021) that assessed the effects of straw retention and straw removal on carbon footprint of continuous corn cropping and corn-soybean rotation ( Song Q. et al, 2021 ). Hence, straw return-to-field usually gives rise to GHG emissions from the soil and increase carbon footprint of agricultural activity ( Dhaliwal et al, 2019 ).…”
Section: Reduction Of the Carbon Footprint Of Straw Return-to-field B...supporting
confidence: 84%
“…Different inputs of chemical fertilizers, human activities, and fuels create variations in carbon emissions from agricultural inputs under different management practices, indirectly influencing the carbon cycling of systems 59,60 . Many studies have reported that the net GWP is affected by the use of inorganic fertilizers, fuel, plastic film, and pesticides in the crop growing season 39,61 .…”
Section: Effect Of Mulching Practices and Urea Types On Net Global Wa...mentioning
confidence: 99%
“…However, it is essential to highlight that the calculated N2O emission intensity does not consider C sequestration induced by the application of biochar and straw, which can change the GHG emission balance from a longterm perspective. Therefore, it fails to account for the soil organic C storage, which contributes to lower the GHG balance from the activity (Bhattacharyya et al, 2022;Guenet et al, 2021;Song et al, 2021).…”
Section: Discussionmentioning
confidence: 99%